2001
DOI: 10.1021/ja0007915
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Solution and Protein-Bound Structures of DNA Duplexes with the Major Intrastrand Cross-Link Lesions Formed on Cisplatin Binding to DNA

Abstract: DNA bases in the three-base-pair (3bp) region of duplexes with the two major lesions of cisplatin (cis-PtCl(2)(NH(3))(2)) with DNA, namely d(XGG) and d(XAG) ( = N7-platinated base), differ in their relative positions by as much as approximately 3.5 A in structures in the literature. Such large differences impede drug design and assessments of the effects of protein binding on DNA structure. One recent and several past structures based on NMR-restrained molecular dynamics (RMD) differ significantly from the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
199
4
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(234 citation statements)
references
References 38 publications
30
199
4
1
Order By: Relevance
“…Furthermore, it has been suggested that the H2' signal should be rather sensitive to deviations from regular double helical conformation [44][45][46]. For example, a large upfield shift of H2' in a cis-platinated duplex was attributed to shielding by the destacked adenine base of the kinked structure [46].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been suggested that the H2' signal should be rather sensitive to deviations from regular double helical conformation [44][45][46]. For example, a large upfield shift of H2' in a cis-platinated duplex was attributed to shielding by the destacked adenine base of the kinked structure [46].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been suggested that the H2' signal should be rather sensitive to deviations from regular double helical conformation [44][45][46]. For example, a large upfield shift of H2' in a cis-platinated duplex was attributed to shielding by the destacked adenine base of the kinked structure [46]. It is now well established that Y-R steps (Y= pyrimidine, R= purine) like CpG are geometrically flexible [47] and several studies have shown that CpG steps are involved in DNA bending [48,49].…”
Section: Methodsmentioning
confidence: 99%
“…Previous NMR studies of Pt-GG adducts have examined a single type of adduct (CP or OX) in a single sequence context and have compared both the proton chemical shifts and NOE cross-peak intensities with average values for undamaged B-DNA in a variety of sequence contexts (24,25,27,33) (34). However, it is unclear whether some of the observed differences are due to differences in sequence context rather than between the platinated and unplatinated strand.…”
Section: Proton Assignmentsmentioning
confidence: 99%
“…However, downfield chemical shifts have been reported for the H8 protons of the 5′ and 3′ G residues for all Pt-GG adducts studied to date (24)(25)(26)33), so this has been considered a universal feature of Pt-GG adducts. In their analysis of a CP-GG adduct, Marzilli et al (25) reported a much greater downfield chemical shift for the H8 proton on the 5′ G residue than for the 3′ G residue and a significant upfield shift of the H2′ proton on the C complementary to the 5′ G residue, which they considered universal features of all CP-GG adducts. However, we do not observe either of these features in direct comparisons of the CP-GG DNA (Table S1) adducts with undamaged DNA (Table S2), so these chemical shifts do not appear to be features of all CP-GG adducts.…”
Section: Proton Assignmentsmentioning
confidence: 99%
See 1 more Smart Citation